Breakdown 2.0? Systemic Blockages in Late-Stage Statism and Late-Stage Liberal Capitalism. (June 2023) - Stalder, Felix
Castells' analysis of the breakdown of Soviet statism is possibly more relevant now than when it was written. By identifying systemic blockages to necessary societal transformation—then from industrialism to informationalism—he offers a framework to analyze the contemporary crisis of liberal democracy. Then and now, the challenges are caused by the system's inability to organize the complexity created by itself which creates more and more internal contradictions. Two current challenges threatening the stability of the liberal democracy are rising social inequality and the crossing of geophysical boundaries of the earth as an ecological system. The inability to address these challenges is related to systemic blockages within liberal democracies. Parallels to the late Soviet Union are drawn without predicting outcomes.